Aqua-puncture: a waterfront rejuvenation strategy for Jabon, Sidoarjo, Indonesia / Fairuz Mutia, Dominikus Aditya Fitriyanto and Azkia Avenzoar - Mutia, Fairuz; Fitriyanto, Dominikus Aditya; Avenzoar, Azkia (2022)
Indonesian urban planning and design haven't prioritized coastline development. On the other hand, many Indonesian cities started as riverfront villages. Jabon, Sidoarjo's waterfront development uses road transit currently, instead of their history as waterways, the urban development relationship was then disregarded. On the other hand, the term aqua-puncture is being used in many regions to restore rivers. In the meantime, an approach known as aqua-puncture has been tested and put into practice in a number of places throughout the world as a method to reinvigorate the interaction between waterways and their potential. The state of the Jabon District is then intriguing and merits further study. As a result, the purpose of this study is to determine the morphology of the waterfront region in the Jabon area and investigate the possibility of applying aqua-puncture to the environmental conditions of the area. This qualitative study employs tissue analysis to identify where an aqua-puncture procedure is needed to restore Jabon's waterfront as a tourist destination. The results show that aqua-puncture could restore the river in various areas. On the eastern bank, cultural-historical values should be restored and utilized. To strengthen spatial cognition, building distinctive sea activities and adapting inland waterways to aquapuncture will lessen global influence.